Continuation theorems for Mönch countable compactness-type set-valued maps. Issue 7 (19th May 2021) - O'Regan, Donal
Abstract : A number of Leray–Schauder-type continuation theorems for general classes of maps are presented in this paper. Our maps will satisfy a countable compactness-type condition.